Mit Helm und Gurt auf dem Weltmarkt. Verkehrsforschung in Schweden. - Borcherding, Anke (Deutscher Verkehrs-Verlag, 2005)
Der schwedische Staat fördert massiv die Sicherung der internationalen Wettbewerbsfähigkeit der nationalen Wirtschaft und Industrie. Die Verkehrsforschung in Schweden befindet sich dementsprechend in einem permanenten strukturellen und thematischen Veränderungs- und Anpassungsprozess. Da Schweden ein Land mit einer eigenen Fahrzeugindustrie ist, werden umfangreiche und kostenintensive Forschungsprogramme zur Fahrzeugentwicklung in Kooperation von Industrie, Forschung und Staat aufgelegt und zum größeren Teil vom Staat finanziert. difu

The government in Sweden champions the international competitiveness of the country's economy and industry. The structure and substance of transport research in Sweden is in constant flux. Because Sweden has its own automotive industry, extensive and cost-intensive research programs on vehicle development are conducted in cooperation with industry, the research community, and the government and are largely financed by the Swedish state. Setting priorities in transport research also seems to come easier to Sweden than to Germany, where authority is shared by the federal government, state governments, and their respective ministries in a way unknown in Sweden. On the whole, Sweden is one of the world's innovative leaders in both applied and basic research on transport, an assessment reflected in the ambitious objectives of the country's transport policy. An outstanding example thereof is "Vision Zero", Sweden's long-term goal of completely eliminating deaths due to accidents. difu
Keywords: Verkehr; Straßenverkehr; Autoverkehr; Verkehrssicherheit; Unfallverhütung; Forschung; Verkehrspolitik; Kraftfahrzeugindustrie; Kraftfahrzeugmarkt; Verkehrsforschung; Fahrzeugentwicklung; Weltmarkt